2021
DOI: 10.1111/oik.08714
|View full text |Cite
|
Sign up to set email alerts
|

Heterospecific pollen deposition is positively associated with reproductive success in a diverse hummingbird‐pollinated plant community

Abstract: Heterospecific pollen deposition (HPD) is ubiquitous across plant communities, especially for generalized species which use a diversity of pollinators, and may have negative effects on plant reproduction. However, it is unclear whether temporal changes in the co‐flowering community result in changes in HPD patterns. Moreover, community‐level studies are required to understand which factors influence HPD and how the reproduction of different species is affected. We investigated the temporal variation of HPD, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 83 publications
1
14
0
Order By: Relevance
“…Among 1249 species from 927 studies in pollen limitation from 1981 and 2015 (Bennett et al, 2018), only four studies involving six species measured the HP effects (see Figure 2 of Ashman et al, 2020). Our findings on the effects of CP and HP on seed set in three Silene species are consistent with a recent investigation that found a positive correlation of fruit set with HPD and a negative correlation of pollen limitation with HPD among 31 hummingbird‐pollinated plant species (Lopes et al, 2022). We propose that plant species with unrestrictive flowers, accessible to generalist pollinators, are more likely to evolve a tolerance strategy to dilute the deleterious effects of HPD.…”
Section: Discussionsupporting
confidence: 93%
“…Among 1249 species from 927 studies in pollen limitation from 1981 and 2015 (Bennett et al, 2018), only four studies involving six species measured the HP effects (see Figure 2 of Ashman et al, 2020). Our findings on the effects of CP and HP on seed set in three Silene species are consistent with a recent investigation that found a positive correlation of fruit set with HPD and a negative correlation of pollen limitation with HPD among 31 hummingbird‐pollinated plant species (Lopes et al, 2022). We propose that plant species with unrestrictive flowers, accessible to generalist pollinators, are more likely to evolve a tolerance strategy to dilute the deleterious effects of HPD.…”
Section: Discussionsupporting
confidence: 93%
“…The potential benefit of co-flowering and offering nectar at similar times is the joint attraction of pollinators (Moeller 2004 ) and increased visitation, which is likely to favor the fitness of plants, especially rare species (Feldman et al 2004 ; Bergamo et al 2020a , b ). Interestingly, a recent study found a positive relationship between heterospecific pollen deposition and fruit set of hummingbird-pollinated plants suggesting that sharing both flowering times and pollinators may promote facilitation and reproductive benefits for plants (Lopes et al 2022 ). Also, because hummingbird-pollinated plants tend to be pollen-limited (Wolowski et al 2013 ), facilitation via co-flowering may help overcome pollen limitation by jointly attracting pollinators (Bergamo et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heterospecific pollen deposition is generally thought to have negative effects on seed production through mechanisms such as stigma clogging, interference in the style, or conspecific pollen loss (Ashman and Arceo‐Gómez, 2013; Moreira‐Hernández and Muchhala, 2019). In practice, however, if pollinators also tend to deposit more conspecific pollen when they deposit more heterospecific pollen, increased heterospecific pollen deposition may actually correspond to greater seed set (e.g., Lopes et al, 2021), especially if the recipient species has evolved a degree of tolerance to heterospecific pollen. For example, in this issue, Hao et al (2023) studied patterns and consequences of heterospecific pollen deposition onto stigmas in three Silene species and found that stigmas receiving more heterospecific pollen also tended to receive more conspecific pollen and that hand‐pollination with mixtures of conspecific and heterospecific pollen did not usually reduce seed production compared to those with only conspecific pollen.…”
Section: Function and Performance In Pollination Or How Pollen Links ...mentioning
confidence: 99%
“…Trait–performance relationships for heterospecific pollen deposition have been less well studied, although analyses of population means suggest that such relationships may occur at least occasionally (Peuker et al, 2020; Lopes et al, 2021). The positive relationships often observed between conspecific and heterospecific pollen loads (e.g., Tur et al, 2016) also suggest that the trait–performance relationships might be similar in shape.…”
Section: Function and Performance In Pollination Or How Pollen Links ...mentioning
confidence: 99%